Mixed Logit Estimation of the Value of Travel Time - Staffan Algers; Pål Bergström; Matz Dahlberg; Johanna Lindqvist Dillén (Uppsala University, Department of Economics, 1998)
In this paper we use mixed logit specifications to allow parameters to vary in the population when estimating the value of time for long-distance car travel. Our main conclusion is that the estimated value of time is very sensitive to how the model is specified: we find that it is significantly lower when the coefficients are assumed to be normally distributed in the population, as compared to the traditional case when they are treated as fixed. In our most richly parameterised model, we find a median value of time of 57 SEK per hour, with the major part of the mass of the value of time distribution closely centred around the median value. The corresponding figure when the parameters are treated as fixed is 89 SEK per hour. Furthermore, our finding that the ratio of coefficients in a mixed logit specification differ significantly from the ones in a traditional logit specification is contrary to the results obtained by Brownstone & Train (1996) and Train (1997). Whether the ratios will differ or not depends on the model and the data generating process at hand.
urn:nbn:se:uu:diva-2422
Keywords: C15; C25; R41; 330; Mixed Logit; Simulation Estimation; Value of Time